A transparent dialogue between iconography and chemical characterisation - Rodrigues, Alexandra (2021)
This work presents the first results of the iconographic study and analytical characterisation of a set of four stained-glass panels that are part of the collection of National Palace of Pena (Sintra, Portugal). These panels were collected by the King Ferdinand II in the mid-nineteenth century, for his main residence the Palace of Necessidades (Lisbon, Portugal), and only first presented to the general public in 2011. This study contributes with the knowledge of Technical Art History and Heritage Science to a better and deeper understanding of their history, materials and techniques used in the production, where an art-historical and a scientific approach are applied to attribute their origins. Based on the analysis of the formal and stylistic characteristic of the panels, it is proposed that the drawings used for the production of three of these panels may be based on the design and painting being carried out in the same workshop, and that the four panels have the same provenance (Germany). The composition of the glass and grisaille was determined and colourising elements were identified. Through this approach, conclusive correlation between the analysed glasses was possible: all are calcium rich or calcium–potassium rich types, and the results also suggest that the same source of silica was used for their production. A typical mixture of glass and lead oxide was found in the grisaille applied on the painted panels. However, less usual was the use of a copper oxide pigment for the black grisaille. All these findings support the proposals made regarding provenance and production period (fifteenth century).